TASAWUF DI TENGAH PERUBAHAN SOSIAL (Studi tentang Peran Tarekat dalam Dinamika Sosial-Politik di Indonesia) - Syamsun Ni’am (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
Sufism – especially tarekat in Indonesia – in its long story has experienced dynamic development. At the early stage of its development, Sufism aimed to lead people to individual piety, to approach the only God, as a response and critique of the widespread deviation based on social-politic conditions committed by the authorities. Then it develops to become a social-political force and supporter of economic force to oppose tyrannical authorities. So Sufism (or tarekat) as if it became a popular religion which continuously develops in the community. In this case, sufism is then not regarded as static and conservative teaching system and religious practice. But it has the dynamic role in developing the world, included in Indonesia.